Critical success factors for financing renewable IPPs in South Africa - Hamilton-Tshangela, Someleze Noxolo (Graduate School of Business (GSB), 2026)
This dissertation investigates the critical success factors in financing Renewable Energy Independent Power Producers (REIPPs) in South Africa, focusing on both programme-level and project-level elements. By analysing financial, regulatory, and operational aspects, the research explores the key elements that impact on the bankability and sustainability of REIPP projects. This study adopted a qualitative research methodology, employing semi-structured interviews as the primary means of data collection. These interviews were conducted remotely via Microsoft Teams, recorded, and transcribed to ensure responses were captured accurately. The interview framework was developed based on extant literature, in particular Gratwick and Eberhard (2016) and Kruger (2021), to explore the programme-level and project-specific success factors influencing South Africa's Renewable Energy Independent Power Producer Procurement (REIPP) programme. A semi-structured approach was employed, incorporating both open- and close-ended questions to enable guided discussions and follow-up questions for deeper insights. This research is grounded in qualitative data collected from 10 interviews with key stakeholders involved in South Africa's REIPP programme. The sample includes two REIPP developers, two financial investors, and six advisors, providing a comprehensive perspective on the programme-level and project-level factors contributing to the programme's success. To assess the effectiveness of South Africa's REIPP programme, this study develops an analytical framework that examines both programme-level and project-level factors. At the programme level, the framework evaluates auction design and implementation, including procurement volume distribution, bidder selection criteria, and the efficiency of auctions in ensuring timely project execution (Kruger, 2021). At the project level, the framework considers determinants of project success, including financial feasibility, technical expertise, regulatory compliance, and stakeholder engagement as key determinants of project success. By integrating these factors, the framework offers a holistic perspective on how procurement mechanisms and project-level dynamics influence the overall effectiveness and sustainability of the REIPP programme thematic analysis of the interview data highlights the critical role of financial accessibility, the creditworthiness of off-takers like Eskom, the availability of skilled contractors, and the adequacy of grid infrastructure in achieving successful project execution. At the programme level, factors such as competitive bidding models, project scale, and regulatory efficiency are essential in ensuring the long-term sustainability of REIPPs. The Sensitivity: MTN Internal study emphasises the importance of well-structured tariff models, transparent bidding processes, and streamlined regulatory frameworks to address current challenges. Key strategic recommendations include enhancing financial mechanisms, increasing investment in grid infrastructure, and ensuring policy consistency to support South Africa's transition to renewable energy. These findings not only apply to South Africa but also offer valuable insights into other emerging economies seeking to develop their renewable energy sectors. Further research is recommended to explore innovative financing strategies, government policies, and long-term project performance to sustain progress in the renewable energy industry.